2022
DOI: 10.1111/and.14571
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of supplementation of cryopreservation medium with gallic acid as an antioxidant in quality of post‐thaw human spermatozoa

Abstract: Human sperm cryopreservation is a way to preserve sperm in the clinic. But, the production of reactive oxygen species (ROS) during cryopreservation, has certain negative impacts on the quality of sperm and its reproductive capacity. The goal of this study is to see how sperm cryopreserved in media enriched with gallic acid alter post-thaw morphology, motility, viability, DNA structure, and plasma membrane lipid peroxidation. Four groups were considered for performing this study: (1) Fresh sperm before cryopres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…46 Studies have linked increased ROS production with significant DNA damage, including changes in the double and single strands of DNA, breakdowns in DNA cross-linking, and changes in chromosome structure. 47,48 The data presented in this study support previous studies by showing that iso leads to increased fragmentation of sperm DNA and that resveratrol's severity is slightly decreased when iso is combined with resveratrol. In the middle stages of spermatogenesis, most DNA damage occurs due to the protamine-histone transition pathway.…”
Section: Discussionsupporting
confidence: 89%
“…46 Studies have linked increased ROS production with significant DNA damage, including changes in the double and single strands of DNA, breakdowns in DNA cross-linking, and changes in chromosome structure. 47,48 The data presented in this study support previous studies by showing that iso leads to increased fragmentation of sperm DNA and that resveratrol's severity is slightly decreased when iso is combined with resveratrol. In the middle stages of spermatogenesis, most DNA damage occurs due to the protamine-histone transition pathway.…”
Section: Discussionsupporting
confidence: 89%
“…Despite some controversy in the literature [24], alterations in sperm morphology following cryopreservation with various protocols have been reported in several studies. Both the percentage of abnormal spermatozoa [25][26][27] and the teratozoospermia index (TZI, i.e., the number of abnormalities/spermatozoon) may increase after the procedure [28]. Most alterations involve tail and acrosome structures.…”
Section: Functional and Structural Damagementioning
confidence: 99%
“…Kumar et al [125] have shown that mitoquinone, a mitochondrial-targeted antioxidant, both attenuates ultrastructural changes and protects several proteins involved in sperm key functions from alterations induced by vitrification. Emerging studies in the last few years have investigated the effects of the supplementation of freezing media with taurine and hypotaurine [145,146], melatonin [147,148] and gallic acid [25] as antioxidants. Some beneficial effects have been reported with taurine and its precursor hypotaurine which slightly but significantly improved sperm parameters, including DNA integrity, when supplemented to extenders both for standard cryopreservation [146] and vitrification [145] methods.…”
Section: Possible Strategies To Prevent the Damage And New Approaches...mentioning
confidence: 99%
“…Evidence indicates that compounds with anti-oxidant properties can improve sperm motility in mammalian spermatozoa by suppressing lipid peroxidation [56][57][58]. Increased lipid peroxidation has been associated with cryopreservation in mammalian spermatozoa [51,[59][60][61]. We did not measure lipid peroxidation in this study.…”
Section: Discussionmentioning
confidence: 93%